GRICE’S COOPERATIVE PRINCIPLE AND EMOJI INTERPRETATION (Ustozlar uchun, 2026)
The article examines H.P. Grice’s theory, centered on the principle of cooperation in linguistic communication. The author explores the hypothesis that language is essential for productive collaboration, drawing parallels with the "yo-he-ho" theory of language origin and the behaviorist "Use Theory of Meaning." Special focus is placed on identifying pragmatic universals through Gricean maxims (Quality, Quantity, Relevance, and Manner). The study also compares Grice’s framework with the Natural Semantic Metalanguage theory developed by A. Wierzbicka and C. Goddard.